2022
DOI: 10.3390/ijerph19159646
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chronotype, Physical Activity and Sedentary Behaviour: A Systematic Review

Abstract: Background: The aim of this systematic review is to compile and assess the scientific evidence about the relationship between chronotypes and physical activity (PA). Methods: A systematic review was executed using a structured electronic search in PubMED, Cochrane Library, PsycInfo and Trip Database. The searches employed keywords such as chronotype, sleep, acrophase, chronotype preference, morningness, physical activity and sedentary, using MeSH terms. JBI critical tools were used to appraise methodological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 56 publications
0
12
1
Order By: Relevance
“…Two extreme types of chronotype, termed morningness (an early bird) and eveningness (a night owl), means having an advanced and delayed sleep period, respectively. Evening chronotype associates with less physical activity 6 and unhealthy dietary habits 7 and thus could potentially have adverse health effects and increase the risk of cancer 8 . A matched case‐control study revealed that patients with gastroenteropancreatic neuroendocrine tumors had more commonly an evening chronotype compared to healthy controls 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Two extreme types of chronotype, termed morningness (an early bird) and eveningness (a night owl), means having an advanced and delayed sleep period, respectively. Evening chronotype associates with less physical activity 6 and unhealthy dietary habits 7 and thus could potentially have adverse health effects and increase the risk of cancer 8 . A matched case‐control study revealed that patients with gastroenteropancreatic neuroendocrine tumors had more commonly an evening chronotype compared to healthy controls 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some systematic reviews showed that the evening chronotype was usually viewed as a potential risk factor while the early chronotype was protective for health-related outcomes (more healthy). [25][26][27] Additionally, healthy sleep duration was defined as 7-9 hours/day according to the National Sleep Foundation's recommendations. 28 Therefore, the five healthy sleep behaviours were defined as (1) early chronotype, (2) 7-9 hours sleep duration per day, (3) never or rare insomnia, (4) no snoring and (5) no frequent daytime sleepiness.…”
Section: Definition Of Sleep Patternsmentioning
confidence: 99%
“…M-types and E-types are also subdivided into moderate and extreme types [ 176 ]. N-types have no circadian preference and can be considered as an intermediate type between M and E-types [ 176 , 177 ]. In comparison to M-types, the E-types have less physical activity and more sedentary time [ 177 ].…”
Section: Physiological Rhythms and Chronotypesmentioning
confidence: 99%
“…N-types have no circadian preference and can be considered as an intermediate type between M and E-types [ 176 , 177 ]. In comparison to M-types, the E-types have less physical activity and more sedentary time [ 177 ]. It should be noted that although sleep is an important dimension, chronotype has multiple dimensions and other factors such as environmental and social influences shape the chronotypes of individuals [ 178 ].…”
Section: Physiological Rhythms and Chronotypesmentioning
confidence: 99%